2009
DOI: 10.1007/s11661-009-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Degassing Behavior of Nanostructured Al and Its Composites

Abstract: The synthesis of bulk ultrafine-grained (UFG) and nanostructured Al via cryomilling can frequently require a degassing step prior to consolidation, partly due to the large surface area of the as-milled powders. The objective of this study is to investigate the effects associated with cryomilling with stearic acid additions (as a process-control agent) on the degassing behavior of Al powders. This objective was accomplished by completing select experiments with Al-7.5Mg, Al-6.4 wt pct Al 85 Ni 10 La 5 , and Al-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…For effective H release, higher degassing temperatures are favorable, but can lead to grain growth. Previous studies have demonstrated an average grain size increase from 25 nm to 78 nm in 12-hour cryomilled Al 14.3 wt pct B 4 C when degassed at temperatures as high as 673 K (400°C) for 14 hours, [10] and from 50 nm to 118 nm in 8-hour cryomilled Al 5083 after degassing for only 2 hours at 773 K (500°C). [12] In addition, the increase of the average grain size with an increasing degassing temperature from 673 K (400°C) to 773 K (500°C) was confirmed; yet, higher degassing temperatures helped eliminate porosity.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For effective H release, higher degassing temperatures are favorable, but can lead to grain growth. Previous studies have demonstrated an average grain size increase from 25 nm to 78 nm in 12-hour cryomilled Al 14.3 wt pct B 4 C when degassed at temperatures as high as 673 K (400°C) for 14 hours, [10] and from 50 nm to 118 nm in 8-hour cryomilled Al 5083 after degassing for only 2 hours at 773 K (500°C). [12] In addition, the increase of the average grain size with an increasing degassing temperature from 673 K (400°C) to 773 K (500°C) was confirmed; yet, higher degassing temperatures helped eliminate porosity.…”
Section: Introductionmentioning
confidence: 93%
“…For instance, cryomilled Al powders are often degassed prior to powder consolidation in an effort to remove the majority of H, which is introduced into the powder through the stearic acid commonly used as a process control agent. [8][9][10] The H, which can lead to hydrogen embrittlement, [11] is adsorbed on the powder surface and can be released through exposure to high temperatures under vacuum. The degassing conditions must be properly selected so that the H is removed yet the nanostructure is retained.…”
Section: Introductionmentioning
confidence: 99%
“…is assigned to the CH 3 group [17,18] . The TG/FT-IR spectra corresponding to TMQ degradation at 362 and 473 °C are shown in Figures 3c and 3d, respectively.…”
Section: Tg/ft-ir Analysis Of Additivesmentioning
confidence: 99%
“…[1,11,12] Although the product of gas atomization is in powder form and is small in size, the amorphous powder can be further processed through various powder metallurgical techniques into engineering MG components. [12][13][14][15] The thermal history experienced by atomized powder is one of the key factors that affect the initial formation and eventual retention of the amorphous phase. To maximize cooling rate, and thereby maximize the extent of amorphous fraction in atomized powders, controllable processing parameters that affect the cooling rate and the solidification process of atomized droplets require careful selection and control, particularly, if optimized GA is the goal.…”
Section: Introductionmentioning
confidence: 99%